Classroom audit: student self-performance, group performance, and tutor performance in a problem-based learning tutorial - Abdus Salam,; Mohd Nasri Awang Besar,; Mohammad Arif Kamaruddin,; Nabishah Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2011)
The educational industry has been the subject of a number of enquiries throughout this century. Although some changes have been made in medical education in recent years, many improvements are still needed. Problem-based learning (PBL) is one of the innovative changes that have been made in many universities all over the world; the Universiti Kebangsaan Malaysia (UKM) Medical Centre has also adopted it as one of its major teaching modalities. A fundamental aspect of the effectiveness of PBL is classroom interpersonal skills. To investigate these interpersonal skills in terms of self-, group, and tutor performance, a questionnaire survey was administered to a group of ten first semester medical students at UKM Medical Centre during mid-2009. In terms of self-performance in decision making, this study revealed that the students made decisions by consensus, while 80% of the students understood other team members and asked questions to clarify. Furthermore, 70% of the students were aware of differences in thinking styles, while 90% were patient listeners. In regard to group performance, 90% of the students felt the group was discussing knowledge, and 100% felt that the group was sharing knowledge. Regarding tutor performance, all students were of the opinion that the tutor established rapport, demonstrated the ground rules of PBL well, and created a non-threatening learning environment. The characteristics of interpersonal skills required in PBL were maintained in this classroom. However, many more students should be aware of the differences in thinking styles among themselves to avoid conflict, and the role of the tutor is very important in this regard. This study reflects the audit of a single PBL classroom. Further audits involving other classrooms are recommended in order to promote organisational performance.